2015
DOI: 10.1093/humrep/dev303
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of ovarian activity by measurement of urinary excretion rates using the Ovarian Monitor, Part IV: the relationship of the pregnanediol glucuronide threshold to basal body temperature and cervical mucus as markers for the beginning of the post-ovulatory infertile period

Abstract: This study (project #90905) was funded by the NDP/UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction (HRP). D.G.C. currently works for a diagnostic development company, Science Haven Ltd. The other authors have nothing to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The present study has confirmed the diversity of hormonal waves in normally cycling women in terms of amplitude, wavelength, relative timing, and wave profile [1,[7][8][9]. This diversity was observed not only between women but also between different cycles in a single woman.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The present study has confirmed the diversity of hormonal waves in normally cycling women in terms of amplitude, wavelength, relative timing, and wave profile [1,[7][8][9]. This diversity was observed not only between women but also between different cycles in a single woman.…”
Section: Resultssupporting
confidence: 85%
“…In our view, hormone profiles are characterized by the occurrence of one or several waves. Each wave exhibits specific characteristics: i) Amplitude reflects the hormone concentration (e.g., follicular stimulating hormone (FSH) shows one peak during the early pre-ovulatory phase and another peak immediately before ovulation; the amplitudes of these two peaks vary between women and between cycles of a given woman [5,6]); ii) Wavelength reflects the duration of the hormone change (e.g., the length of the luteinizing hormone (LH) peak may range from a single day to about a week [7,8]); iii) Timing relative to the other hormone waves (e.g., during the luteal phase, the onset of the progesterone plateau may occur immediately before or after ovulation [9,10]); iv) Profile, which may have a triangular, arch, or plateau form [1]. Describing a hormonal profile requires that each of these four characteristics be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly used markers such as basal body temperature may be useful as well for the end of the fertile window ( 18 ) but may be less precise ( 19 ). In addition, development of urinary hormone monitors that provide quantitative results for various hormones may give relevant detailed information to determine whether an individual woman’s levels were changing from her particular baseline ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the sampling regime, the void volume and, often, the time between voids vary, so it is necessary to account for the resulting changes in quantitative assays of any urinary analyte (Brown et al, 2018). The natural approach wherever high quality data are required is simply to measure the urine production rate, as has routinely been done by users of the Ovarian Monitor (Brown et al, 1989;Blackwell et al, 2003;Blackwell et al, 2012;Blackwell et al, 2013;Blackwell et al, 2016). The analyte excretion rate is then calculated by multiplying the analyte concentration by the urine production rate .…”
Section: Introductionmentioning
confidence: 99%